2015
DOI: 10.1111/nicc.12159
|View full text |Cite
|
Sign up to set email alerts
|

The effects of music therapy in endotracheal suctioning of mechanically ventilated patients

Abstract: It is recommended that music therapy should be added to the routine nursing care for mechanically ventilated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 58 publications
(94 reference statements)
3
40
0
1
Order By: Relevance
“…The findings of this study were similar to those of other studies conducted with different populations by Korhan et al [59], Yaman Aktaş and Karabulut [60], and Lee et al [61], in which no significant changes in the HR were observed in patients who received MT. In contrast, Raglio et al [30] evaluated the effects of MT and found an increase in HR variability in patients receiving MT, suggesting a possible improvement in cardiovascular function.…”
Section: Discussionsupporting
confidence: 81%
“…The findings of this study were similar to those of other studies conducted with different populations by Korhan et al [59], Yaman Aktaş and Karabulut [60], and Lee et al [61], in which no significant changes in the HR were observed in patients who received MT. In contrast, Raglio et al [30] evaluated the effects of MT and found an increase in HR variability in patients receiving MT, suggesting a possible improvement in cardiovascular function.…”
Section: Discussionsupporting
confidence: 81%
“…To explore a reduction in pain severity, which is in agreement with the study of Yaman Aktaş and Karabulut [19] with a two-sided 5% significance level (α = 0.05) and a power of 90%, a sample size of 40 patients per group was necessary, given an anticipated dropout rate of 10%. According to Jacob Cohen’s effect size coefficients, the sample size should comprise at least 40 people to have a large effect size ( d = 0.40).…”
Section: Methodsmentioning
confidence: 99%
“…It also results in the reduction of pain intensity by causing encephalin and endorphin release [10, 15, 16]. A recent study on 66 mechanically ventilated patients reported that pain scores during ES were lower in the music group than in the control group [19]. ES is the process of cleaning pulmonary secretions from an artificial airway and is identified as among the most painful and stressful ICU intervention due to anxiety over transient loss of breathing or chocking [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suctioning is accompanied by pain, fear, and sensations of suffocation commonly associated with patients’ loss of breath (3, 12). According to published research, most adult patients in ICUs experience pain and agitation resulting in physical and psychological complications that may last many years after discharge from the hospital (13).…”
Section: Introductionmentioning
confidence: 99%